Improved basic life support skills and patient transportation at ambulance drivers in Medan Tuntung and Medan Sunggal area to improve patient safety - Yetty Machrina; Siregar, Kamal Basri; Nuraiza Meutia; Gema Nazri Yanni; Yunita Sari Pane (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The technique of providing basic and quick life support (BHD) and transportation to patients with cardiac and pulmonary arrest can save a patient's life. An ambulance driver as one of the ambulance personnel should be equipped with the two forms of skills above. The aim of community service is to increase the capacity of ambulance drivers in terms of providing basic life support skills and patient transportation to improve patient safety. This training was held in September 2019, at the H. Adam Malik General Hospital Training Center Installation Medan, with 24 participants. The training is carried out with 2 methods, namely exposure to BHD theory and BHD skills training. The knowledge and skills of participants before and after the training were assessed. Pre and post assessment results were analyzed using paired t-test with a significance level of p <0.05 Ambulance drivers in the Medan Tuntung and Medan Sunggal area are mostly over 30 years old, with most working as ambulance drivers for more than 5 years. The most recent level of education is high school graduation or equivalent. The results of statistical analysis using paired t-test, obtained a significant difference in the knowledge of ambulance drivers about basic life support theory before and after training (p = 0.000). Likewise, ambulance driver skills in providing basic life support for adult patients, infants and children were significantly different before and after training (p = 0.000). Training in basic life support skills and patient transportation can increase the capacity of ambulance drivers in providing basic life support..